PENERAPAN TEKNIK PROBING DAN PROMPTING TERHADAP RASA INGIN TAHU DAN HASIL BELAJAR SISWA PADA MATERI REAKSI REDUKSI OKSIDASI BERBANTU GOOGLE FORM PADA MASA PANDEMI COVID 19 DI SMA NEGERI 4 PADANGSIDIMPUAN - Fatma Suryani Harahap; Heni Mulyani Pohan; Elisa Elisa; Rabiyatul Adawiyah Siregar; Nur Sahara; Nurkholidah Siregar; Sahlan Tuah (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2024)
The application of probing and prompting techniques is the application of science and technology by conducting investigations or examinations by relating questions in the form of cause and effect aimed at encouraging or guiding the achievement of satisfactory learning outcomes. The application of probing and prompting techniques as a source of independent learning because it requires the involvement of students in exploring and guiding learning. The application of probing and prompting techniques is expected to make students more interactive in learning. So that student curiosity can increase in accordance with the expected learning objectives. This research was motivated because probing and prompting techniques had never been applied at SMA Negeri 4 Padangsidimpuan. This study aims to determine whether there is an influence of the application of probing and prompting techniques on students' curiosity and learning outcomes on oxidation reduction reaction material in class X MIA SMA Negeri 4 Padangsidimpuan. The data on the curiosity test of students in the experimental class was with an average of 49.37 and in the control class was with an average of 49.17, so students' curiosity was higher in the experimental class. Then classes that used Probing and Promting techniques obtained an average learning outcome test of 36.47 to 79, so there was an increase.